2003
DOI: 10.1038/oby.2003.53
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐Chain Triglycerides Increase Energy Expenditure and Decrease Adiposity in Overweight Men

Abstract: ST-ONGE, MARIE-PIERRE, ROBERT ROSS, WILLIAM D. PARSONS, AND PETER J.H. JONES. Medium-chain triglycerides increase energy expenditure and decrease adiposity in overweight men. Obes Res. 2003;11:395-402. Objective: The objectives of this study were to compare the effects of diets rich in medium-chain triglycerides (MCTs) or long-chain triglycerides (LCTs) on body composition, energy expenditure, substrate oxidation, subjective appetite, and ad libitum energy intake in overweight men. Research Methods and Procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
142
3
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(167 citation statements)
references
References 35 publications
11
142
3
3
Order By: Relevance
“…Similar results were obtained when 24 healthy overweight men were fed MCTo for 28 days [38]. In concert with the favorable changes in the lipid profile, these participants exhibited a decrease in upper adipose tissue measured through magnetic resonance imaging [39].…”
Section: Introductionsupporting
confidence: 68%
“…Similar results were obtained when 24 healthy overweight men were fed MCTo for 28 days [38]. In concert with the favorable changes in the lipid profile, these participants exhibited a decrease in upper adipose tissue measured through magnetic resonance imaging [39].…”
Section: Introductionsupporting
confidence: 68%
“…Similarly, medium-chain triacylglycerol (MCT) enhances fat metabolism due to its distinct metabolic pathway. 27 Previous studies in humans show increased postprandial EE and fat oxidation after both acute 7 and repeated 28,29 MCT feeding, supporting the reduced weight gain observed with chronic 30 MCT consumption. St Onge et al reported that MCT increased fat oxidation and EE in a 4-week crossover feeding studies including both women 28 and men.…”
Section: Discussionmentioning
confidence: 89%
“…St Onge et al reported that MCT increased fat oxidation and EE in a 4-week crossover feeding studies including both women 28 and men. 29 MCT intake increased daily EE, extrapolated from 6.5 h of indirect calorimetry data, which equated to 50 kcal day À1 in women and 43 kcal day À1 in men by the end point of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Nagao et al have reported that the ingestion of tea rich in catechins for four weeks reduced body fat by 0.5 kg, 37) and St-Onge et al have reported that the ingestion of medium-chain triacylglycerols for four weeks reduced body fat by 0.8 kg. 38) Since the ingestion of CH-19 Sweet for two weeks reduced body fat by 0.6 kg, CH-19 Sweet is suggested to be as effective for reducing body fat as such compounds as catechins and medium-chain triacylglycerols.…”
Section: Discussionmentioning
confidence: 99%